Comparison of Graft Uptake in Perforated Eardrums with and without Myringosclerosis: A Prospective Case-control Study in a Tertiary Centre - Ayaz Rehman; Faizah Ashfah Latief Deva; Asef Ahmad Wani; Majid Masoodi; Bashir Malik; Owais Makhdoomi (International Archives of Otorhinolaryngology)
Introduction Various factors have been reported to affect the rates of success after tympanoplasty, among them, myringosclerosis. However, there are few studies focusing only on the effect of myringosclerotic plaque removal on tympanoplasty outcomes.